Cell-free and concentrated ascites reinfusion therapy (CART) for management of massive malignant ascites in gastric cancer patients with peritoneal metastasis treated with intravenous and intraperitoneal paclitaxel with oral S-1. Issue 7 (July 2015) - Yamaguchi, H.; Kitayama, J.; Emoto, S.; Ishigami, H.; Ito, T.; Hanafusa, N.; Watanabe, T.
Abstract Background Massive malignant ascites originating from peritoneal metastasis of gastric cancer is difficult to control and resistant to chemotherapy. Cell-free and Concentrated Ascites Reinfusion Therapy (CART) is one of the types of apheresis therapy, by which filtered and concentrated ascites containing albumin and globulin is reinfused intravenously to patients. We retrospectively studied the feasibility of intraperitoneal (IP) chemotherapy combined with CART in gastric cancer patients with massive malignant ascites. Methods Paclitaxel (PTX) was administered via an IP access port implanted in the subcutaneous space. If patient had massive ascites at the start of treatment, paracentesis was performed through a percutaneous IP catheter and then CART was performed. PTX was administered through the catheter until the ascites diminished. Results A total of 127 CART procedures in 30 patients were analyzed. The average volume of processed ascites was 3.1 L, which was concentrated to 0.33 L containing 85.5 g protein on average. Significant increases in urine volume, serum total protein and albumin level were found after the CART. Increase in body temperature (0.3 °C), decrease in platelet count (3.8 × 104/μl), and changes in blood pressure (2 mm Hg) were found after the CART procedure, but no clinically significant adverse event was experienced. The median survival time and 1-year survival of 30 patients who received IP chemotherapy combined with the CART procedure was 10.2 months and 43.3% respectively. Conclusions IP chemotherapy combined with CART might be a promising strategy for patients with massive malignant ascites originating from peritoneal metastasis of gastric cancer.